Diversity and community of methanogens in the large intestine of finishing pigs - Mi, Jiandui (BMC Microbiol, 2019)
BACKGROUND: Methane emissions from pigs account for 10% of total methane production from livestock in China. Methane emissions not only contribute to global warming, as it has 25 times the global warming potential (GWP) of CO(2), but also represent approximately 0.1~3.3% of digestive energy loss. Methanogens also play an important role in maintaining the balance of the gut microbiome. The large intestines are the main habitat for the microbiome in pigs. Thus, to better understand the mechanism of methane production and mitigation, generic-specific and physio-ecological characteristics (including redox potential (Eh), pH and volatile fatty acids (VFAs)) and methanogens in the large intestine of pig were studied in this paper. Thirty DLY finishing pigs with the same diet and feeding conditions were selected for this experiment. RESULT: A total of 219 clones were examined using the methyl coenzyme reductase subunit A gene (mcrA) and assigned to 43 operational taxonomic units (OTUs) based on a 97% species-level identity criterion. The family Methanobacteriaceae was the dominant methanogen in colonic digesta of finishing pigs, accounting for approximately 70.6% of the identified methanogens, and comprised mainly the genera Methanobrevibacter (57%) and Methanosphaera (14%). The order Methanomassiliicoccales, classified as an uncultured taxonomy, accounted for 15.07%. The methanogenic archaeon WGK1 and unclassified Methanomicrobiales belonging to the order of Methanomicrobiales accounted for 4.57 and 1.37%, respectively. The Eh was negative and within the range − 297.00~423.00 mV and the pH was within the range 5.04~6.97 in the large intestine. The populations of total methanogens and Methanobacteriales were stable in different parts of the large intestine according to real-time PCR. CONCLUSION: The major methanogen in the large intestine of finishing pigs was Methanobrevibacter. The seventh order Methanomassiliicoccales and species Methanosphaera stadtmanae present in the large intestine of pigs might contribute to the transfer of hydrogen and fewer methane emissions. The redox potential (Eh) was higher in the large intestine of finishing pigs, which had a positive correlation with the population of Methanobacteriale.